Perbandingan Trombosit dengan Antikoagulan K2EDTA - Syuhada Syuhada; Abdurrohman Izzuddin; Hendri Yudhistira (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: difficulty in taking patient blood samples often occurs in obese patients, newborns, and blood sampling in patients with small veins also causes insufficient blood volume collection. Objective: to determine whether there is a difference between the results of the platelet hematology examination in the blood sample volume of 3 mL, 2 mL, and 1 mL with the anticoagulant K2EDTA. Methods: This study used an observational analytic method with a cross-sectional design. calculate. Results: The mean number of platelets in the blood volume of 2 mL and 3 mL in the vacutainer tube was higher than that of the 1 mL blood sample. Conclusion: There is no significant difference in the results of the comparison of platelet counts between blood volumes of 1 mL, 2 mL, and 3 mL in the K2EDTA vacutainer tube